In-depth blood immune profiling of Good syndrome patients - Torres-Valle, Alba; Aragon, Larraitz; Silva, Susana L.; Serrano, Cristina; Marcos, Miguel; Melero, Josefa; Bonroy, Carolien; Arenas-Caro, Pedro Pablo; Casado, David Monzon; Olaizola, Pedro Mikel Requejo; Neirinck, Jana; Hofmans, Mattias; et al. (Frontiers in Immunology, 2023)
Good syndrome (GS) is a rare adult-onset immunodeficiency first described in 1954. It is characterized by the coexistence of a thymoma and hypogammaglobulinemia, associated with an increased susceptibility to infections and autoimmunity. The classification and management of GS has been long hampered by the lack of data about the underlying immune alterations, a controversy existing on whether it is a unique diagnostic entity vs. a subtype of Common Variable Immune Deficiency (CVID). Here, we used high-sensitive flow cytometry to investigate the distribution of up to 70 different immune cell populations in blood of GS patients (n=9) compared to age-matched CVID patients (n=55) and healthy donors (n=61). All 9 GS patients displayed reduced B-cell counts -down to undetectable levels (<0.1 cells/μL) in 8/9 cases-, together with decreased numbers of total CD4+ T-cells, NK-cells, neutrophils, and basophils vs. age-matched healthy donors. In contrast, they showed expanded TCRγδ+ T-cells (p≤0.05). Except for a deeper B-cell defect, the pattern of immune cell alteration in blood was similar in GS and (age-matched) CVID patients. In depth analysis of CD4+ T-cells revealed significantly decreased blood counts of naïve, central memory (CM) and transitional memory (TM) TCD4+ cells and their functional compartments of T follicular helper (TFH), regulatory T cells (Tregs), T helper (Th)2, Th17, Th22, Th1/Th17 and Th1/Th2 cells. In addition, GS patients also showed decreased NK-cell, neutrophil, basophil, classical monocyte and of both CD1c+ and CD141+ myeloid dendritic cell counts in blood, in parallel to an expansion of total and terminal effector TCRγδ+ T-cells. Interestingly, those GS patients who developed hypogammaglobulinemia several years after the thymoma presented with an immunological and clinical phenotype which more closely resembled a combined immune humoral and cellular defect, with poorer response to immunoglobulin replacement therapy, as compared to those in whom the thymoma and hypogammaglobulinemia were simultaneously detected. Our findings provide a more accurate definition of the immune cell defects of GS patients and contribute to a better discrimination among GS patients between those with a pure B-cell defect vs. those suffering from a combined immunodeficiency with important consequences on the diagnosis and management of the disease.